Exclusively Breastfeeding and Hypernatremic Dehydration - MK Çağlar; FŞ Altugan; I Özer (Tehran University of Medical Sciences, 2005)
There is no doubt that breast-feeding is the best and safest way of feeding infants. Physiological weight loss occurs in the first two or three days of life, and the achievement of birth weight is expected towards the end of the first week. Hypernatremic dehydration may occur in exclusively breast-fed infants if milk supply is low during these first few days. It is not because of the high sodium content in breast milk; it is because of insufficient lactation. That is, the main cause of hypernatremic dehydration is water deprivation. There are many causes for low milk intake. Since most causes are preventable or able to be improved, mothers, particularly first time mothers, should receive more reassurance and practical advice in the technique of breast-feeding. Before their discharge from the hospital, they should be educated about the associated features of unsuccessful breast-feeding, such as going to the breast infrequently or for short times, infrequent passage of urine and stool, jaundice, lethargy, irritability and fever. Late diagnosis may cause catastrophic outcomes, such as a variety of palsies, apnea, bradycardia, seizures, hypertension, disseminated intravascular coagulation, necrotising enterocolitis after establishing full oral feeds, amputation of an extremity secondary to arterial thrombus, multiple cerebral infarctions, intracranial hemorrhages, massive intra ventricular hemorrhage, multiple dural thromboses. If babies are weighed on the day of the Guthrie test, those in the early onset of a disease and those who could not achieve their birth weight can be easily identified. The latter should be closely followed.